Tradisi Bersih Desa Dan Sedekah Bumi Desa Sindurejo - Ferianto, Anggun Eko; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2024)
Village cleaning and earth almsgiving are traditions carried out to cleanse the village from calamities. This tradition was initially implemented because a plague or epidemic struck the residents of Sindurejo Village, and it is also a way to express gratitude for the bountiful harvests provided by God. The tradition of village cleansing and earth offering preserved in Sindurejo Village, Gedangan District, Malang Regency, is carried out every month of Suro and is considered a form of respect to the ancestors who have contributed and is also seen as a medium for gathering, deliberating, and strengthening solidarity among fellow villagers. This research has the following objectives: 1) to describe the history, form, and meaning of the local wisdom of the village clean-up and earth donation tradition in Sindurejo Village, 2) to describe the values contained in the local wisdom of the village clean-up and earth donation tradition in Sindurejo Village, and 3) to describe the values of local wisdom of the village clean-up and earth donation tradition in Sindurejo Village as a source for social studies learning. This research uses field research methods, including interviews, documentation, and observation. These methods are used to find information related to the village clean-up and earth donation tradition. The researcher organizes the data using qualitative methods.